Conceptions of Learning by Adult Students at The Institute of Education Development Universiti Teknologi MARA, Shah Alam - Hassan Basri, Fazimah Hayati (2005)
This is a qualitative study on the conceptions of learning held by adult students enrolled in the distance education program the Institute of Education Development (InED), Universiti Teknologi Mara (UiTM), Shah Alam. Conceptions of learning can be defined as the beliefs and ideas people have about what learning actually means. Specifically the objectives of this study are to describe the meaning of learning as perceived by students in the distance education program at InED, UiTM and to identify the relationships between their conceptions of learning and the learning approaches and whether these conceptions were in congruence with those established in previous studies. In line with the objectives above, this study takes on the qualitative research method that is deemed appropriate when the intent of the researcher is to understand a phenomenon. For this purpose, this study adopted the qualitative research approach known as phenomenology. The purpose of this approach is to determine what an experience means for the person who have had the experience and are able to provide a comprehensive description of it. The sample for this study consisted of 15 students involved in the distance education program at UiTM and the individual interview become the predominant method to gather data. A micro cassette and a guide interview list were used to aid in capturing the conversation during the interview sessions. The interviews were then transcribed verbatim and translated. From the data analysis, themes were developed which described the phenomena. Findings showed that four themes were identified among the students. These conceptions of learning consisted of as 1) acquiring knowledge, 2) applying the acquired knowledge, 3) constructing meanings and new understandings and 4) changing as a person. This study also revealed that from the themes uncovered the students were more closely bound to the deep approach to learning while the surface approach was not evident. Basically this study concluded that four different themes of conceptions of learning were identified with all of the themes linked to the deep approach. This study also concluded that the results concurred with previous research in the same area. Finally it is recommended that a follow up study be conducted to explore the relationship between these conceptions and approaches to learning with the outcome of learning and with lecturers' conceptions of teaching with the hope that educators would be able to better facilitate and help students gain maximum benefits from the process of learning.